Convergent close-coupling calculations of positron scattering on metastable helium - Utamuratov, R.; Kadyrov, Alisher; Fursa, Dmitry; Bray, Igor; Stelbovics, Andris (American Physical Society, 2010)
The convergent close-coupling method has been applied to positron scattering on a helium atom in the 2 S-3 metastable state. For this system the positronium (Ps) formation channel is open even at zero scattering energy making the inclusion of the Ps channels especially important. Spin algebra is presented for the general case of arbitrary spins. A proof is given of the often-used assumption about the relationship between the amplitudes for ortho-positronium and para-positronium formation. The cross sections for scattering from 2 3S are shown to be significantly larger than those obtained for the ground state.